Vertical Transport, Entrainment, and Scavenging Processes Affecting Trace Gases in a Modeled and Observed SEAC4RS Case Study. Issue 11 (10th June 2020) - Cuchiara, G. C.; Fried, A.; Barth, M. C.; Bela, M.; Homeyer, C. R.; Gaubert, B.; Walega, J.; Weibring, P.; Richter, D.; Wennberg, P.; Crounse, J.; Kim, M.; et al.
Abstract: The convectively driven transport of soluble trace gases from the lower to the upper troposphere can occur on timescales of less than an hour, and recent studies suggest that microphysical scavenging is the dominant removal process of tropospheric ozone precursors. We examine the processes responsible for vertical transport, entrainment, and scavenging of soluble ozone precursors (formaldehyde and peroxides) for midlatitude convective storms sampled on 2 September 2013 during the Studies of Emissions, Atmospheric Composition, Clouds and Climate Coupling by Regional Surveys (SEAC 4 RS) study. Cloud‐resolving simulations using the Weather Research and Forecasting with Chemistry model combined with aircraft measurements were performed to understand the effect of entrainment, scavenging efficiency (SE), and ice physics processes on these trace gases. Analysis of the observations revealed that the SEs of formaldehyde (43–53%) and hydrogen peroxide ( 80–90%) were consistent between SEAC 4 RS storms and the severe convection observed during the Deep Convective Clouds and Chemistry Experiment (DC3) campaign. However, methyl hydrogen peroxide SE was generally smaller in the SEAC 4 RS storms (4%–27%) compared to DC3 convection. Predicted ice retention factors exhibit different values for some species compared to DC3, and we attribute these differences to variations in net precipitation production. The analyses show that much larger production of precipitation between condensation and freezing levels for DC3 severe convection compared to smaller SEAC 4 RS storms is largely responsible for the lower amount of soluble gases transported to colder temperatures, reducing the amount of soluble gases which eventually interact with cloud ice particles. Key Points: Formaldehyde and hydrogen peroxide scavenging efficiencies are consistent with literature, while methyl hydrogen peroxide is generally smaller Highly soluble hydrogen peroxide is mostly depleted between cloud base and the freezing level, that is, the warm region of the storm Retention of dissolved trace gases in frozen precipitation seems to be more important for moderately soluble trace gases